Inclusive policy development from the ground up: insights from the household water-energy-food nexus - Al-Zu’bi, Maha; Mabhaudhi, T.; Daher, B.; Brouziyne, Youssef (Elsevier, 2025)
Despite substantial contemporary research and a growing trend in exploring the water-energy-food (WEF) nexus, most research efforts have been invested in macro-level supply-side infrastructure and policies. However, prioritizing demand-side management policies can provide new opportunities and untapped potential for addressing interconnected resource challenges. Demand management inherently encompasses users’ consumption patterns, behaviors, socio-economic conditions, and choices, thereby necessitating active engagement and participation. Understanding household-level demands is fundamental to assess the demand for and consumption of water, energy, and food, as well as to inform policy decisions. In this context, our study investigated household consumption patterns within the interconnected WEF nexus, including daily practices such as cooking and washing, conservation measures, household governance, and their cross-cutting relationships with climate change. As a case study, we conducted our research in the Jabal Al Natheef neighborhood of Amman City, Jordan. Our findings reveal that households can propose and enact climate-friendly decisions. Significant gender-related differences were also observed in decisions made across WEF household practices. Additionally, households’ perspectives highlighted governance issues and revealed gaps in policy implementation along with the need for more inclusive decision-making processes. Our results underscore the importance of understanding household-level WEF nexus dynamics and daily practices in informing environmental policies, particularly those related to climate action. Such policies are best developed from the bottom-up by incorporating household insights, rather than relying solely on top-down, one-size-fits-all solutions.